Microtus xanthognathus ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
143. Taiga Vole Microtus xanthognathus French: Campagnol a joues jaunes / German: Gelbwangen-Wihlmaus / Spanish: Topillo de taiga Other common names: Chestnut-cheeked Vole, Yellow-cheeked Vole Taxonomy. Arvicola xanthognatha [sic] Leach, 1815, Hudson Bay, Manitoba, Canada. This species is monotypic. Distribution. C Alaska, USA, E across Yukon, W Northwest Territories, extreme NW British Columbia, N & C Alberta, N Saskatchewan, and N Manitoba to W Hudson Bay, Canada. Descriptive notes. Head-body 141-173 mm, tail 45-53 mm, hindfoot 24-— 27 mm; weight 140-170 g. The Taiga Vole is large and distinctive, with orange or yellow color near snout and whiskers. Dorsum is dark sepia to bister (brownish yellow), with coarse black hair. Venter is dusky gray. Juveniles are dark gray. Skull is ridged and angular and has large bullae. Nasals and incisive foramina are elongated and narrow. M” has three closed triangles; M, has two nearly enclosed triangles. Chromosomal complement is 2n = b4, FN = 62. Habitat. Early ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 338, DOI: 10.5281/zenodo.6707142 ...